2017
DOI: 10.1177/0272431617737624
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Influence of Executive Functions, Effortful Control, Empathy, and Social Behavior on the Academic Performance in Early Adolescents

Abstract: In this study, we explored the predictive role of behavioral measures of Executive Functions (EFs) and a self-report measure of Effortful Control (EC) on the academic performance of early adolescents. We also analyzed the mediating role of self-reported empathy and social behavior rated by peers (i.e., prosocial behavior and social preference) and by the lead teacher (i.e., social competence). A sample of 244 adolescents aged between 12 and 13 years participated in the study. The resulting structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Our findings emphasize the protective role of self-regulation (as indexed by a greater HRV after the SRS) among students with an inhibited temperament. Hence, secondary school students—particularly when their individual characteristics place them at risk for academic difficulties—may benefit from interventions supporting self-regulatory strategies (Zorza, Marino, & Acosta Mesas, 2017). A number of programs exist that promote self-regulation in school-age children (e.g., Fishbein et al, 2016) that may be effective with students with inhibited temperaments.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings emphasize the protective role of self-regulation (as indexed by a greater HRV after the SRS) among students with an inhibited temperament. Hence, secondary school students—particularly when their individual characteristics place them at risk for academic difficulties—may benefit from interventions supporting self-regulatory strategies (Zorza, Marino, & Acosta Mesas, 2017). A number of programs exist that promote self-regulation in school-age children (e.g., Fishbein et al, 2016) that may be effective with students with inhibited temperaments.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cognitive empathy didn't moderate the relation between fear of COVID-19 and stress consequences which overturned our hypothesis. Previous studies show that cognitive empathy is related to executive function (84,85), especially inhibitory control, which may help us to inhibit emotional contagion to regulate our concern about others when we empathize with others (86). Studies have shown that the inhibitory control of individuals would be reduced under negative emotions (87)(88)(89).…”
Section: The Moderating Role Of Empathymentioning
confidence: 99%
“…Hendry et al ([81] p. 2) characterized EF as involving "higher-order self-regulatory processes". The processes include inhibitory control, cognitive flexibility and working memory [24,74,[82][83][84]. Blair ([70] p. 3) said of EF that it involves "the ability to hold information in working memory, to inhibit fast and unthinking responses to stimulation, and to flexibly shift the focus of one's mental frame, is more or less the foundation for the intentional, volitional self-directed control of behavior.…”
Section: Key Concepts and Processes In General Self-regulationmentioning
confidence: 99%
“…Commonality between EF and EC has been found via a "cognitive control" factor that included temperament-rated inhibitory control and performance on EF inhibitory control tasks [80]. Nevertheless, there is also evidence that behavioral measures of EF and self-report measures of EC in adolescents could predict academic performance in complementary and independent ways [83]. At least in adolescents, Zorza et al [83] argued that EF and EC share some elements, but do not completely overlap.…”
Section: Key Concepts and Processes In General Self-regulationmentioning
confidence: 99%
See 1 more Smart Citation